INVENTORY INFORMATION SYSTEM OF GOODS USING CODEIGNITER FRAMEWORK - Azis, Muhammad Rais; Hadi Sirad, Mochammad Apriyadi (Patria Artha Technological Journal, 2019)
This type of research is experimental, namely by designing, manufacturing and testing the system model. This inventory information system aims to manage inventory data, incoming goods data and item data out at the real store. The testing method on this system uses black box testing which aims to find out functions that do not work well or errors from a system. From the results of testing on the modules in this system, namely logins, units, goods, incoming goods, outgoing goods, incoming goods and reports of outgoing goods can function properly. The inventory system that has been built can help a true store in terms of managing goods data, incoming goods data and outgoing item data